Solitary Bee Life History Traits and Sex Mediate Responses to Manipulated Seasonal Temperatures and Season Length - Slominski, Anthony H.; Burkle, Laura A. (Frontiers in Ecology and Evolution, 2019)
The effects of climate change on solitary bee species, the most diverse and abundant group of wild pollinators, remain poorly understood, limiting our ability to forecast consequences for bee-plant interactions and pollination services. Life history traits, such as overwintering life stage, sex, and body size may influence solitary bee responses to climate change by mediating the effects of temperature on physiological processes spanning fall, winter, and spring. Yet, most studies assessing the effects of temperature on solitary bees have focused on managed species and have isolated the effects of winter temperature. Here, we reared male and female individuals representing eight cavity-nesting solitary bee species that overwinter either as adults (i.e., Osmia spp.) or prepupae (i.e., Megachile spp.). Eight rearing treatments were used, in which we manipulated fall and spring temperature, fall duration, and the timing of spring onset. We measured pre-emergence mortality, pre-emergence weight loss, emergence timing, and post-emergence lifespan. We found that Osmia spp. responded primarily to the timing of spring onset, whereas Megachile spp. responded primarily to spring temperature. Early-spring onset increased both pre-emergence mortality and pre-emergence weight loss and reduced post-emergence lifespan in Osmia spp. In addition, treatments caused unequal shifts in the timing of emergence between male and female Osmia spp. By contrast, warmer spring temperature decreased weight loss and increased lifespan in Megachile spp. These findings suggest that Osmia spp. may be more vulnerable to negative fitness consequences of climate change compared to Megachile spp., and that climate change may have implications for population-level sex-ratios and mating success in species of Osmia. This work helps build a mechanistic understanding of how life histories may mediate solitary bee responses to climate change, and how these responses may impact solitary bee fitness and plant-bee interactions.